If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -9) = 20 Reorder the terms: 4(-9 + x) = 20 (-9 * 4 + x * 4) = 20 (-36 + 4x) = 20 Solving -36 + 4x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + 4x = 20 + 36 Combine like terms: -36 + 36 = 0 0 + 4x = 20 + 36 4x = 20 + 36 Combine like terms: 20 + 36 = 56 4x = 56 Divide each side by '4'. x = 14 Simplifying x = 14
| 12c^3+9c= | | 2y+46=3y-4 | | 4(3c-1)-4=8c+8 | | 2y+46=34y-4 | | 20b^3= | | 20b^3-25a= | | x-5=-4+7 | | 20y^2u^7v^4= | | z-62+30z=18+15z | | 28y^3v^8= | | 0.025x+3(0.50)=0.038x | | 3(2n-1)=2(-4n+1) | | 6(x-5)/3=2 | | 0.025x+0.50=0.038x | | z+78=2z-2 | | x/4+3=8 | | 4(z-4)+6z-2= | | 6t(t-5)=0 | | 4x^2*32=5 | | 3t^2-2t^3=0 | | -1-7x=83 | | 2-4x-x=x+8 | | 15+16+4n=130 | | 6x-8=-32 | | z+72=2z-3 | | 14x+72=31 | | -6x-8=-14 | | x^2=31y+28 | | -12x=50+8 | | 8-4x=-16 | | x^4-14641=0 | | 160+64t-16t^2=0 |